Perancangan Sistem Informasi Korespondensi Berbasis Website Pada Kantor Pertanahan Kota Tangerang - Kurniawan, Rano; Zahruddin, Muhamad; Shintia, Mira (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2019)
Every organization, be it an organization in the community, company or organization in the government environment, conducts activities or correspondence activities with each of its stakeholders. Correspondence activity is a communication activity that occurs between the organization and its stakeholders. Of course, this correspondence activity aims to ensure that the ongoing correspondence process can proceed as planned accordingly. The same is true of what happened at the Tangerang city land office. However, the correspondence system applied at the Tangerang city land office at this time, especially incoming mail, is still not integrated and computerized in terms of data storage, inputting, searching, and printing of disposition sheets and reports every month. This of course results in a process of inputting and reporting that requires relatively long time. So by doing this research, a correspondence information system design was made at the Tangerang city land office and the stages. The method used in this research is object oriented analysis and design. The programming language used in this study is with PHP and MySQL as the database and testing the system using black box testing. The results of this study are in the form of an information system design consisting of incoming letter input, disposition of the letter according to purpose, receipt of the letter by the intended person and the form of reporting. With the creation of a correspondence information system at the Tangerang city land office, it is expected to minimize the occurrence of errors during the data collection process, storage, data search and report generation that does not take a long time and is able to display report results in accordance with existing data. This correspondence information system can be presented to support and improve the performance of staff and other employees who are directly involved in it. Keywords: Designing, Information Systems, Correspondence, Inbox, Tangerang City Land Office.